The fifth discipline the art and practice of the learning organization - Senge, Peter M. (New York Currency, 2006)
This revised edition of Peter Senge?s bestselling classic, The Fifth Discipline, is based on fifteen years of experience in putting the book?s ideas into practice. As Senge makes clear, in the long run the only sustainable competitive advantage is your organization?s ability to learn faster than the competition. The leadership stories in the book demonstrate the many ways that the core ideas in The Fifth Discipline, many of which seemed radical when first published in 1990, have become deeply integrated into people?s ways of seeing the world and their managerial practices.
Includes bibliographical references and index.
Keywords: Organizational effectiveness